Nurse Stress in the Perspective of Interpersonal Communication and Organisational Climate - Rusdianto Rusdianto; Nefi Darmayanti; Nina Siti Salmaniah Siregar (Psikostudia : Jurnal Psikologi, 2023)
The phenomenon that occurs during the pandemic due to work stress presents complex problems in the perspective of interpersonal communication and organizational climate. This study aims to determine the influence of interpersonal communication and organizational climate on the stress of nurses at Tk. IV IM 0701 Hospital Lhokseumawe. The subjects in the study were 148 nurses with total sampling techniques. Nurse stress is measured by a factor scale consisting of 22 valid items, interpersonal communication is measured by the De Vito interpersonal communication aspect scale there are 18 valid items, organizational climate is measured by the organizational climate dimension scale according to Litwin and Stringer there are 18 valid items. Data analysis using multiple regression. The results concluded that there is an influence of interpersonal communication and organizational climate on nurses' work stress Freg coefficient value = 22.171 with p < 0.05, correlation coefficient R = 0.545 with p < 0.05 and R2 = 0.297, the second hypothesis is the influence of organizational climate on nurse work stress with t value = 2.223 with p <0.05, and the third hypothesis is the influence of interpersonal communication on nurse work stress with t value of 5.394 with p < 0.05. Therefore, research related to work stress, nurses must adopt interpersonal communication well, as well as a pleasant organizational climate.Fenomena yang terjadi di masa pandemi akibat stres kerja maka menghadirkan masalah yang kompleks dalam perspektif komunikasi interpersonal dan iklim organisasi. Penelitian ini bertujuan untuk mengetahui pengaruh komunikasi interpersonal dan iklim organisasi terhadap stres perawat Rumah Sakit Tk. IV IM 0701 Lhokseumawe. Subjek dalam penelitian sebanyak148 perawat dengan tekhnik Total Sampling. Stres perawat diukur dengan skala faktor terdiri dari 22 item yang valid, komunikasi interpersonal diukur dengan skala aspek komunikasi interpersonal De Vito ada 18 item yang valid, iklim organisasi diukur dengan skala dimensi iklim organisasi menurut Litwin dan Stringer ada 18 item yang valid. Analisa data menggunakan regresi ganda. Hasil penelitian menyimpulkan adanya pengaruh komunikasi interpersonal dan iklim organisasi terhadap stres kerja perawat nilai koefisien Freg=22.171 dengan p < 0.05, koefisien korelasi R = 0.545 dengan p<0.05 dan R2 = 0.297, hipotesis kedua adanya pengaruh iklim organisasi terhadap stres kerja perawat dengan nilai t = 2.223 dengan p <0.05, dan hipotesis ketiga adanya pengaruh komunikasi interpersonal terhadap stres kerja perawat dengan nilai t sebesar 5.394 dengan p < 0.05. Oleh karena itu penelitian yang berkaitan dengan stress kerja perawat harus mengadopsi komunikasi interpersonal dengan baik demikian pula terhadap iklim organisasi yang menyenangkan.